(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article discusses the significance of sanogenic education, its integration into the native language subject, and the anticipated practical outcomes. Additionally, the process of implementing specific methods for completing these tasks with students is presented.